2015
DOI: 10.1063/1.4922285
|View full text |Cite
|
Sign up to set email alerts
|

Achieving reversibility of ultra-high mechanical stress by hydrogen loading of thin films

Abstract: Nano-materials are commonly stabilized by supports to maintain their desired shape and size. When these nano-materials take up interstitial atoms, this attachment to the support induces mechanical stresses. These stresses can be high when the support is rigid. High stress in the nano-material is typically released by delamination from the support or by the generation of defects, e.g., dislocations. As high mechanical stress can be beneficial for tuning the nano-materials properties, it is of general interest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 45 publications
2
41
0
Order By: Relevance
“…Thicker (30 nmþ) Pd layers clamped to substrates can develop folds, cracks, and even peel off. 17 Thinner films (as in our case) can withstand much larger deformations, 18 however for both thicker and thinner films, one may also expect an effect of hydrogen annealing 19 which may modify the crystal structure of Pd. Our previous studies showed that some irreversible changes to our films can indeed occur during their first exposure to hydrogen gas, especially diluted H 2 (see e.g., Fig.…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…Thicker (30 nmþ) Pd layers clamped to substrates can develop folds, cracks, and even peel off. 17 Thinner films (as in our case) can withstand much larger deformations, 18 however for both thicker and thinner films, one may also expect an effect of hydrogen annealing 19 which may modify the crystal structure of Pd. Our previous studies showed that some irreversible changes to our films can indeed occur during their first exposure to hydrogen gas, especially diluted H 2 (see e.g., Fig.…”
Section: Methodsmentioning
confidence: 68%
“…17 Thin films, as in our case, can withstand huge stresses due to the clamping effect without deformation. 18 In contrast to single-layer Pd films used in Refs. 17 and 18, our films represent multilayers.…”
Section: Discussionmentioning
confidence: 99%
“…4. Note that all films leave the elastic regime at certain H concentrations, leaving De elast as an upper bound, not reached here [52]. In detail, at De plast (Ds plast ) the channel of plastic stress relaxation opens in the films, e. g. by the emission of new dislocations at the film-substrate interface.…”
Section: Discrete Stress Relaxations (Dsr)mentioning
confidence: 98%
“…On the contrary, similar to other interface effects, the overall effect of PMA on macroscopic material parameters (e.g., on its FMR response) does not noticeably depend on Pd thickness above some critical thickness for the onset of PMA (on the order of several atomic layers) and increases with a decrease in Co thickness. Thin Pd layers can withstand huge compressive stresses without buckling . Hence, by exploiting an interface effect instead of a bulk one the problem of irreversible deformations can be naturally avoided.…”
Section: Discussionmentioning
confidence: 99%